Association of the TG/HDL-C and Non-HDL-C/HDL-C Ratios with Chronic Kidney Disease in an Adult Chinese Population - Jia Wen; Yiyin Chen; Yun Huang; Yao Lu; Xing Liu; Honghao Zhou; Hong Yuan (Karger Publishers, 2017)
Background/Aims: Evidence indicates a role for dyslipidemia in the development of chronic kidney disease (CKD). However, the association of lipid abnormalities and their ratios with kidney disease using the new CKD Epidemiology Collaboration (CKD-EPI) equation is not well understood. Methods: This cross-sectional study included 48,054 adult subjects. CKD was defined as an estimated glomerular filtration rate <60 ml/min/1.73 m2 or dipstick-positive proteinuria. Logistic regression models were used to examine the relationship between lipid variables and CKD. Results: The prevalence of CKD in this study was 3.7%. When the participants exhibited higher serum triglyceride (TG), a higher TG/high-density lipoprotein cholesterol (TG/HDL-c) ratio or a higher non-HDL-c/HDL-c ratio or HDL-c in a lower quartile, the prevalence of CKD tended to be higher. The multivariate adjusted odds ratios for CKD per 1 standard deviation increase in lipid level were 1.17 (1.10-1.23) for TG, 0.86 (0.79-0.93) for HDL-c, 1.21 (1.13-1.31) for the TG/HDL-c ratio, and 1.14 (1.06-1.22) for the non-HDL-c/HDL-c ratio. No significant association was detected between CKD and total cholesterol (TC), non-HDL-c or the low-density lipoprotein cholesterol/HDL-c (LDL-c/HDL-c) ratio. Conclusion: In this relatively healthy adult Chinese population, the CKD-EPI equation determined that the TG/HDL-c and non-HDL-c/HDL-c ratios as well as TG and HDL-c correlate with the prevalence of CKD.